Designing nickel base alloys for microstructural stability through low γ-γ′ interfacial energy and lattice misfit. (15th February 2018) - Meher, S.; Carroll, M.C.; Pollock, T.M.; Carroll, L.J.
Abstract: An extended stability alloy design strategy for multicomponent γ-γ′ nickel-base alloys with near-zero lattice misfit and as low as possible interfacial energy was investigated by isothermal annealing of two experimental alloys at 900 °C for times up to 256 h. The coarsening behavior of the spherical γ′ precipitates and the phase compositions determined by atom probe tomography were utilized to exploit a modified Lifshitz-Slyozov-Wagner relationship to estimate the interfacial energies. The estimated interfacial energies are much lower than predicted by a CALPHAD-based software as well as those typically reported for multicomponent γ-γ′ nickel alloys. Despite successfully minimizing the interfacial energy and γ-γ′ lattice misfit, these factors alone were not sufficient to impart high temperature extended stability through reduced coarsening kinetics. Graphical abstract: Image 1 Highlights: Two experimental nickel-base super alloys exhibited low γ-γ' interfacial energy and a near-zero lattice mismatch. Interfacial energies estimated from experiments were much lower than simulated values. Utilization of experimentally-determined interfacial energies in simulations yield better predictions. The low interfacial energies and lattice misfits did not impart significantly improved γ' coarsening resistance.